Standardized Workload Indicator Staffing Need Method Calculates Hospital Human Resource Requirements: Metode Workload Indicator Staffing Need Terstandarisasi Menghitung Kebutuhan Sumber Daya Rumah Sakit - Dia Nita Efendi; Mia Nasrida Putri; Stifani Yuli Ranti Kobo; Sumartik Sumartik (Proceedings of The ICECRS, 2024)
General Background Human resource planning ensures organizational productivity by matching personnel availability with task demands. Specific Background At Aisyiyah Siti Fatimah Tulangan Hospital, inconsistent personnel calculations across multiple departments caused unjustified labor increments and operational inefficiencies. Knowledge Gap Previous workforce evaluations lacked a uniform standardized approach, resulting in unaligned data specifically for the pharmacy, laboratory, and registration administration units. Aims This study measures labor demands and personnel balance utilizing a unified framework to standardize workforce planning across all clinical departments. Results Quantitative analysis revealed an available working time of 113,460 minutes annually alongside a standard allowance factor of 0.1786. The calculations identified a deficit of one employee in both the pharmacy and laboratory units, which require 15 and 10 personnel respectively. Conversely, the registration administration unit exhibited a surplus of three employees compared to the calculated requirement of 11 staff members. Novelty This research resolves previous organizational misalignments by formulating a unified mathematical standardization for all clinical departments based on realistic task constraints. Implications Institutional management must implement strategic recruitment for understaffed units and execute personnel transfers for departments with surplus labor to sustain operational productivity. Highlights: Quantitative analysis identified an available working time of 113,460 minutes annually for clinical personnel. Pharmacy and laboratory departments experience personnel deficits requiring immediate recruitment strategies. The registration administration department exhibits a labor surplus necessitating internal personnel transfers. Keywords: Personnel Planning, Labor Demands, Operational Productivity, Task Analysis, Clinical Management.